(3Md GdeSCdI GdgfOSjI GdehLhOI aj eJf GdTeSjIs - (3CMeO GdQeVGfi Hf eMSf GdhjROi (B((3GdhRjQi(B)s; (3fLe GdOjf YeQ Hf Ydj GdbRhjfj, GdcdHjs
(3ChdgG (B:s
(3GdMeO ebOGQ GdRhGjG hGdfXGQ s
(3BNQgG (B:s
(3hgPG eGJjSQ dfG ef GdcdGe ef JhVjM gPG GdebGe s
(3hQO Ydi GdfSNI Cf GdTeSjI ddJaJGRGfi hGdUMjM CfgG ddbRhjfi hYdjgG TQM dSYO GdOjf GdJaJGRGfis
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdQjGVjGJ (B- (3bSe (B3 - (3U (B43 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1063s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs